We Probably Thought That Would Be True: Perceiving Complex Emotional States in Nonhumans - Raymond Pierotti; Cynthia Annett (Ethnobiology Letters, 2014)
Review of:Do Fish Feel Pain? Victoria Braithwaite. 2010. Oxford University Press, New York. Pp. 256. $35.00 (hardcover). ISBN 9780199551200.How Animals Grieve. Barbara J. King. 2013. University of Chicago Press, Chicago. Pp. 208, 7 halftones. $25.00 (cloth). ISBN 9780226436944.